A guide for the pharmacist's role in insulin pump management during transitions of care. Issue 3 (12th November 2020) - Clements, Jennifer N.; Castelli, Gregory; Meade, Lisa T.; Odom, Jessica M.
Abstract: In the United States, approximately 12% of the adult population has a diagnosis of diabetes mellitus (DM). Persons with DM are at a higher risk of microvascular and macrovascular complications, as well as hospitalizations, compared with the general population. Over the years, technology for diabetes management has evolved as approximately 350 000 patients are using insulin pump therapy to manage DM. Insulin pump therapy has been shown to improve glycemic control and lower the risk of safety events, such as hypoglycemia. Some studies have shown high compliance with an insulin pump policy among staff members during a hospitalization for a patient with an insulin pump. Other studies have shown improved glycemic control during hospitalization for patients who were managed on an insulin pump from an outpatient endocrinology clinic prior to admission. However, none of the studies involved pharmacy‐ or pharmacist‐led service for insulin pump management during transitions of care. Therefore, we defined the responsibilities of clinical pharmacists, in various roles, regarding insulin pump management in transitions of care. The purpose of this paper is to summarize current evidence for continuous subcutaneous insulin infusion (CSII) in transitions of care, including the use of insulin pumps in the hospital. Opportunities for a pharmacist's role in policies and procedures are also outlined, along with training of clinical pharmacists in this area of practice.